Quadratic multiple regression model and spectral relaxation approach to analyse stagnation point nanofluid flow with second-order slip. (February 2020) - Kumar, B; Seth, GS; Nandkeolyar, R
The present paper is concerned to study the influence of second-order slip, mixed convection, viscous and Joule dissipations, thermophoretic and Brownian diffusions on steady stagnation point nanofluid flow over a stretching sheet embedded in a porous medium with passive control of nanoparticles. Graphs for velocity, temperature and concentration of present nanofluid flow model, obtained by using spectral relaxation method, are discussed in detail for various parameters. Apart from it, present results are verified by previously available results as well as regression analysis is performed for the local Nusselt number for making this model more effective in industries and engineering. From the statistical analysis of local Nusselt number, it is suggested that small variation in thermophoretic parameter leads to large perturbation in local Nusselt number in comparison to Brownian motion parameter, and the presence of Eckert number leads to strengthen Brownian and thermophoretic diffusions.